Manufacturing Mennonites : Work and Religion in Post-War Manitoba - Thiessen, Janis, 1971- (Book collections on Project MUSE., 2013)
Complemented with interviews with workers, managers, and business owners, Manufacturing Mennonites pioneers two important new trajectories for scholarship - how religion can affect business history, and how class relations have influenced religious history.